Analisis Hukum Gay-Lussac Tentang Fluida Pada Kaleng Parfum (Dalam Kajian Studi Literatur) - I Ketut Mahardika; Singgih Bektiarso; Hita Mara Cecilia; Ira Wanda Rahyuni Pitri; Berlian Marsha Malihah; Mafaza Nuris Sabeta (Peneliti.net, 2023)
We often know that when reading perfume products made from cans at the bottom there is a warning that is to keep it below 15ºC-21ºC stating that perfume cans should not be at high temperatures because it will cause the cans to explode caused by the expansion of the gas inside. in a perfume can. Based on a study of Gay-Lussac's law observed by Joseph Louis Gay-Lussac which relates to pressure, volume and temperature of a gas. This law was created when Joseph Louis Gay Lussac boarded a hot air balloon and produced a formula that reads